Parental depressive symptoms and child behavior problems: exploring the role of interactive repair during mother-child interactions - Kemp, Christine, author; Lunkenheimer, Erika, advisor; MacPhee, David, committee member; Steger, Michael, committee member (Colorado State University. Libraries, 2012)
This study examined the role of interactive repair during a challenging task in the relationship between parental depressive symptoms and child behavior problems in a sample of 3.5-year-old children and their mothers (N=100). This study used data collected from parents as well as data collected during live observations in the laboratory setting. Dynamic Systems-based methods were used to measure interactive repair (i.e., returning to a positive interaction after a negative behavior) during mother-child interactions. Findings suggest that interactive repair partially mediates the relationship between maternal depressive symptoms and child internalizing behaviors. These results highlight the potential protective role of interactive repair related to child behavior problems in the context of maternal depressive symptoms. Implications of these findings for parental depressive symptoms and child behavior problems are discussed.
Keywords: child behavior problems; parent-child interaction; child development